Teams and Team ProjectsDifferences in Online and On-campus Adult Learners’ Perceptions. - Judy K. Favor (Adult Education Research Conference, 2015)
Adult students’ perceptions of teams in accelerated business cohorts were examined in six areasteam attraction, performance expectation alignment, workload distribution, intrateam conflict, teamwork preference, and learning. Most students preferred individual work and did not believe teams positively impacted their learning, with more distinct perspectives among adult students in online programs.
Keywords: group projects; adult learners; distance learning; learning teams; cooperative learning